Removing energy from a spacecraft using tethers - Ferreira, Alessandra F.S. [UNESP]; Moraes, Rodolpho V. [UNESP]; Prado, Antonio F.B.A.; Winter, Othon C. [UNESP] (My University, 2019)
For a mission whose focus is the capture of the spacecraft by the main body or a close approach for observation, removing energy from a spacecraft can be an important maneuver. An option is the Tethered Slingshot Maneuver (TSSM) that consists of a cable anchored on the surface of a celestial body with the spacecraft attached to the other end. During the maneuver, the tether rotates by a given angle from the instant the spacecraft is connected to the cable. When detaching from the cable the spacecraft follows a new trajectory. The TSSM is recommended to be made in small bodies, because in this case the size of the tether does not need to be too large. This present paper shows an application of this type of maneuver for Jupiter-Themisto and Jupiter-Carpo systems. The study is numerical, based in the integration of the equations of motion of the spacecraft. Maps of solutions show the energy and inclination variation of the spacecraft relative to the main body for conditions where the spacecraft is decelerated, so reducing its energy. Captures also occur and they are analyzed in the present study.
Keywords: Orbital maneuvers; Removal of energy; Spacecraft; Tether; Tethered Slingshot Maneuver